A critical analysis of the performance of plate- and point-electrodes for determination of electrical properties of the soil mass. (November 2016) - Susha Lekshmi, S.U.; Jayanthi, Prathyusha N.V.; Aravind, P.; Singh, D.N.; Baghini, Maryam Shojaei
Highlights: Plate and point electrodes for electrical properties measurement of geomaterials are compared. Zone of the electric field generated across the electrodes is quantified by COMSOL Multiphysics®. Dimensions of the electrodes and electric field generated across the electrodes are related. Simulated results were critically evaluated with those obtained from the impedance analysis. Abstract: In the recent past, researchers have started utilizing electrical properties of the soil mass for its characterization by employing either plate- or point electrodes. Though, plate-electrodes are easy to use for laboratory experiments, and quantification of geometrical characteristics of the electric field generated within them is easy to quantify, their application for in-situ experiments and for samples of cylindrical shape becomes difficult. On the other hand, usage of point-electrodes which are cylindrical in shape, are used for moisture content determination of the soil or migration of contaminants in it, for coarse-grained soils and fine-grained soils might yield erroneous results, due to the presence of inter particle voids and presence of cavities & anomalies, respectively. Furthermore, quantification of geometrical parameters of the electric field of point-electrodes is quite difficult which results erroneous measurements in determination of electrical properties of the material, in which they are installed. Hence, establishment of the uniqueness of electrical properties obtained from the plate- and point-electrodes, for identical samples becomes utmost important. With this in view, COMSOL Multiphysics® was employed to simulate the electrical response of various geomaterials in their uncontaminated and contaminated states and results were critically evaluated vis-à-vis those obtained from the impedance analysis (1 Hz to 40 MHz). Efforts have also been made to relate the geometrical dimensions of electrodes and electric field generated across the point electrodes, which would facilitate proper design and installation of sensors in a material to achieve the desired output. This study demonstrates the suitability and versatility of the point-electrodes for various (field and laboratory) applications where in moisture profiling and contaminant transport is to be established.